Preliminary Study of Synthesis of Sodium Manganese Oxide Using Sol-Gel Method as Sodium Ion Battery Material - Muhammad Ilham Bayquni; Bambang Sunendar Purwasasmita; Susanto Sigit Rahardi (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2020)
Sodium ion battery is one of the promising alternatives to lithium ion battery. Sodium manganese oxide as the sodium ion battery catode material has been synthesized by modifying the sol-gel method used to obtain lithium manganese oxide. The precursors used were table salt and manganese chloride. The sol-gel process used was water solvent, citric acid as a chelating agent and chitosan as the template. Thermal decomposition and formation zone obtained from simple thermal analysis using furnace and digital scales. Calcination was carried out at 600°C and 850°C for 2 hours. Crystal properties and morphology were analyzed using XRD and SEM. Based on the analysis of XRD pattern, sodium manganese oxide crystals (Na0.7MnO2.05 JCPDS 27-0751) have been formed at both of the calcination temperature. Observed morphology of the sample showed the domination Mn3O4 JCPDS 18-0803 in accordance with crystalline phase identification. These results demonstrate that the modified sol-gel method could be used to obtain sodium manganese oxide as sodium ion battery cathode material.